Fluoride concentration in Malaysian drinking water. - Shaharuddin, Mohd Sham; Yusoff, Mohd Kamil; Yaziz, Mohd Ismail; Ramli, Mohammad Firuz; Ismail, Syazwan Aizat; Abdullah, Mohd Yunus (IDOSI Publications, 2009)

(untitled)
This study aimed at determining the mean concentration of fluoride in drinking water from nine sites in Malaysia. Three sites were in Selangor, one each in Perak, Melaka, Kelantan, Terengganu and the Federal Territory of Kuala Lumpur and one in Kota Kinabalu, Sabah. A total of 689 households were chosen from which a total of 2067 water samples were collected. They were obtained from two sources – treated piped water from water treatment plants (WTPs) and groundwater extensively used for cooking and drinking purposes. Samples were collected from pipes at homes or water buckets from wells. They were then stored in pre-cleaned HDPE bottles and were analysed within the next 72 hours using a direct reading spectrophotometer model DR/2010 HACH Brand. Results showed that the mean concentration of fluoride in Sri Serdang, Selangor was the highest, at 0.71 + s.d 0.12 mg/L, while the concentration of fluoride in the samples from Kota Kinabalu had the lowest mean concentration of fluoride, at 0.08 + s.d 0.06 mg/L. Kelantan, Terengganu and Sabah states have ceased fluoridation of treated water in the wake of higher cases of dental fluorosis amongst the population, which explained the lowest mean concentration of fluoride from sites in these states. The mean concentrations of fluoride in the majority of samples were lower than the concentration recommended by the health authorities i.e. 0.5 – 0.7 mg/L, hence insufficient for eradicating dental caries. This was the main reason why fluoride has been added into treated water. However, higher oncentrations of fluoride i.e. 1 mg/L or more may alleviate the occurrence of dental fluorosis, especially among children.